Ultrastructural analysis of the surface of stainless steel endodontic instruments before and after use - Popović Jelena; Gašić Jovanka; Živković Slavoljub; Mitić Aleksandar; Nikolić Marija; Barac Radomir (Serbian Medical Society - Dental Section, Belgrade, 2014)
Introduction. Although many studies have reported various advantages of nickel-titanium endodontic instruments, the use of stainless steel endodontic files still presents a standard in everyday practice. The aim of this study was to evaluate ultrastructure of the surface of stainless steel endodontic instruments before and after their use. Material and Methods. Fourteen sets of non-used stainless steel endodontic reamers and files were included in the study. Each set of instruments was used one, three or six times in simulated clinical conditions on extracted maxillary premolars. After their use the instruments were subjected to cleaning and sterilization procedures. Ultrastructure of the surface of instruments was observed under scanning electron microscope (SEM). Surface analysis was performed based on the number of uses and size of instruments. The following characteristics were analyzed: defects of instrument flutes, defects of cutting edges and instrument deformations. Results. SEM analysis showed defects on the surface of non-used instruments as a result of the manufacturing process. Surface defects, defects of cutting edges as well as flutes deformations were observed after a single use and were more often noticed in small sized instruments. After three uses, flutes deformations were observed in all small sized instruments and some of the medium size. After six uses all groups of instruments showed defects of cutting edges. Conclusion. Non-used stainless steel endodontic instruments showed surface defects created by the manufacturing process. Defects of cutting edges and flutes can be observed after a single use. To minimize complications and mistakes during clinical preparation it is recommended to limit the number of instrument uses.